Multimedia Learning Environments for Enhancing Students' Analytical Thinking - Seejinda, Manutchaya (Ratchaphruek Journal, 2020)
Learning environments for enhancing students’ critical thinking can be referred to as web-based learning media which have been designed and developed based on the Constructivist theory. They promote learners’ knowledge and critical thinking through the principles of Constructivist learning environments. This model for learning activity was designed by integrating web-based learning media and Constructivist learning theory. It consists of media features and media symbol systems to facilitate learners’ learning, and its design was based on critical thinking. The essential elements are as follows: 1) Problem base; 2) Resources; 3) Analytical thinking support center; 4) Scaffolding; 5) Reading comprehension support center; 6) Intelligence tools; 7) Collaboration; and 8) Coaching. Learning environments for promoting students’ critical thinking could enable learners to compartmentalize or classify elements of one particular matter with specified criteria. In addition, with such learning environments, learners will be equipped with abilities to identify the causal relationship among components as well as to categorize issues or matters with shared features.